A cemented carbide reinforced silicon-manganese bainite steel and a method for producing the same

CN122959611APending Publication Date: 2026-10-23HANDAN HUIQIAO COMPOSITE MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611166265.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

上述方法虽在特定体系内提升了界面结合强度与材料韧性,但是,无有效技术方案将TiC与B4C协同引入硅锰贝氏体基体中,以同时实现强基体与硬质相弥散强化的双重效果,并解决界面结合与致密化问题

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122959611A_ABST
    Figure CN122959611A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of wear-resistant material manufacturing, and discloses a cemented carbide reinforced silicon-manganese bainite steel and a preparation method thereof. The preparation method of the cemented carbide reinforced silicon-manganese bainite steel comprises the following steps: firstly, mixing modified TiC particles, modified B4C particles and a CoCrFeNiAl2Ti2 high-entropy alloy binder phase to sinter a cemented carbide; secondly, pouring silicon-manganese bainite molten steel into a ladle provided with a rare earth magnesium-silicon-iron alloy and the cemented carbide, and then performing slag skimming and casting; and finally, performing heat preservation at 920-950 DEG C and salt bath treatment at 280-320 DEG C to obtain the cemented carbide reinforced silicon-manganese bainite steel. The preparation method of the cemented carbide reinforced silicon-manganese bainite steel is optimized, and the prepared cemented carbide reinforced silicon-manganese bainite steel has high strength, high hardness, excellent impact toughness and excellent wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of wear-resistant material manufacturing technology, and in particular to a cemented carbide-reinforced silicon-manganese bainitic steel and its preparation method. Background Technology

[0002] The performance requirements for steel in fields such as engineering machinery, mining equipment, molds, and high-end tools are becoming increasingly stringent. These requirements not only demand high hardness and excellent wear resistance, but also sufficient toughness to withstand impact loads, good machinability, and cost-effectiveness. Traditional methods for increasing steel hardness primarily involve increasing carbon content or adding large amounts of carbide-forming elements (such as Cr, Mo, and V), which significantly reduces ductility, toughness, and weldability. Furthermore, introducing carbides (such as WC and TiC) or ceramic particles to form metal matrix composites is also an important means of improving wear resistance. However, traditional ceramic-steel composites suffer from poor interfacial bonding, uneven particle distribution, and difficulties in sintering and densification.

[0003] Bainitic steel, especially silicomanganese-based bainitic steel, possesses a unique combination of high strength, high toughness, and good work hardening ability due to its lath bainitic ferrite structure with no or little carbide content, making it a highly promising matrix material. However, the hardness and wear resistance of its pure matrix are still insufficient for extremely harsh wear conditions. Therefore, introducing hard phases (such as carbides, nitrides, and borides) is an effective way to improve the wear resistance of steel materials. Among them, titanium carbide (TiC) and boron carbide (B4C) are known ceramic reinforcing phases with extremely high hardness (TiC: 2800-3200 HV, B4C: 3800-4300 HV) and good chemical stability. In existing technologies, the main methods for introducing TiC or B4C into the steel matrix are powder metallurgy and external addition methods. Powder metallurgy is costly and inefficient, making it difficult to manufacture large-sized parts. The reinforcing phase particles introduced by external methods (such as casting and stirring) have weak bonding with the matrix, which easily leads to stress concentration at the interface, becoming crack sources and impairing material properties.

[0004] To improve the performance of hard phase reinforced steel matrix composites, the following methods are mainly adopted: First, casting and electroslag metallurgy are used to increase the alloy density and strengthen the hard phase bonding force by remelting with consumable electrodes. Second, friction stirring generates heat to make the steel matrix on the blade surface plastic, mechanically stirring in the high-hardness reinforcing phase to form a uniformly dispersed metallurgical bonding layer, which significantly improves the sharpness, wear resistance, and toughness of the blade. Third, a spray deposition composite combined with subsequent isothermal annealing process is used to eliminate interface defects by using atomic diffusion, constructing a dual-scale boride particle bundle reinforcement in situ within the high-manganese steel matrix. By forming a micro-metallurgical bonding interface, macro-interface stress concentration is effectively eliminated, achieving a high-strength bond between the reinforcing phase and the matrix interface. Fourth, interface modification design is implemented, such as adding rare earth elements to improve interface wettability or constructing a gradient coating layer to alleviate stress concentration. Fifth, a composite casting process is developed, which controls the proportion of the reinforcing phase through the design of the preform's pore structure and uses pressure infiltration to promote molten filling. While the aforementioned methods improve interfacial bonding strength and material toughness within specific systems, there is no effective technical solution to synergistically introduce TiC and B4C into a silicon-manganese bainitic matrix to simultaneously achieve the dual effects of strong matrix and dispersion strengthening of the hard phase, and to solve the interfacial bonding and densification problems. Therefore, there is an urgent need to provide a cemented carbide-reinforced silicon-manganese bainitic steel and its preparation method. Summary of the Invention

[0005] In view of this, the present invention provides a cemented carbide-reinforced silicon-manganese bainitic steel and its preparation method.

[0006] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: This invention provides a cemented carbide-reinforced silicon-manganese bainitic steel and its preparation method, comprising the following steps: S1. Modified TiC particles, modified B4C particles, and CoCrFeNiAl2Ti2 high-entropy alloy binder phase are mixed evenly, then heated to 1200~1350℃ for sintering, and cooled to obtain cemented carbide; wherein, in S1, the modified TiC particles are TiC particles coated with transition metal element coating, and the modified B4C particles are B4C particles coated with metal oxide coating. S2. The raw materials of silicon-manganese bainitic steel are smelted. The molten silicon-manganese bainitic steel with a Si content of 2.13%~2.36% is heated to 1653~1668℃ and then poured into a ladle containing rare earth magnesium silicon ferroalloy and the hard alloy in sequence from bottom to top. The slag is removed and the casting is completed to obtain the casting. S3. The casting is kept at 920~950℃ and then subjected to a salt bath at 280~320℃ to obtain hard alloy reinforced silicon manganese bainitic steel.

[0007] Compared to existing technologies, the method for preparing hard alloy-reinforced silicon-manganese bainitic steel provided by this invention introduces a transition metal element coating on the surface of TiC particles. During sintering, this transition metal element coating can melt to form a liquid phase bridge, significantly improving its wetting angle with the CoCrFeNiAl2Ti2 high-entropy alloy binder phase and preventing the formation of interface voids. The metal oxide layer on the surface of modified B4C particles inhibits the excessive diffusion of B element into the CoCrFeNiAl2Ti2 high-entropy alloy binder phase, avoiding the large-area formation of the (Fe,Cr)2B brittle phase and instead forming finer particles. The TiB2 nano-precipitated phase further strengthens the interface; the CoCrFeNiAl2Ti2 high-entropy alloy binder phase acts as a sintering aid, improving its wettability and interfacial bonding ability with silicon-manganese bainitic steel. Among them, Al and Ti elements tend to form carbide or oxide reaction layers at the interface between the CoCrFeNiAl2Ti2 high-entropy alloy binder phase and silicon-manganese bainitic steel, driving reactive wetting and reducing the equilibrium contact angle level; at the same time, the specific binder phase can also improve the hardness and toughness of cemented carbide through good interfacial coherence, thereby improving the performance of cemented carbide-reinforced silicon-manganese bainitic steel.

[0008] Through research, the inventors discovered that when the silicon content in the molten steel of silicon-manganese bainitic steel is too high, the resulting microstructure of the steel becomes significantly coarser, its strength and toughness decrease, and its hardness also drops significantly. This invention further limits the Si content in the molten steel of silicon-manganese bainitic steel. A specific Si content can increase the activity of carbon in austenite. During the growth of bainite and ferrite, excess carbon is discharged into the adjacent austenite on the interface side. Because Si hinders cementite precipitation, the surrounding austenite becomes carbon-rich, stabilizing the carbon-rich residual austenite between or within the bainitic ferrite lamellae, forming carbide-free bainite. Simultaneously, Si also increases the temperature range at which the first type of temper brittleness occurs in the steel, allowing the steel to be tempered at higher temperatures and further eliminating quenching stress. Furthermore, a specific Si content can shift the CCT curve or TTT curve of cemented carbide-reinforced silicon-manganese bainitic steel to the lower right, improving the hardenability and toughness of the bainite.

[0009] In S3, a specific holding temperature ensures full austenitization of the casting, while simultaneously promoting the dissolution and diffusion of Al and Ti elements from some cemented carbide particles into the austenite, forming an interfacial diffusion layer. A specific salt bath temperature guarantees the bainitic phase transformation, thereby improving the strength, toughness, and hardness of cemented carbide-reinforced silicon-manganese bainitic steel. Furthermore, the high silicon content in the molten steel effectively inhibits cementite precipitation during the holding process, refines the bainite laths, and stabilizes the thin-film retained austenite. Through the TRIP effect, it absorbs crack propagation energy, compensates for the brittleness loss caused by the introduction of modified TiC and modified B4C particles, and ensures the strength, toughness, and wear resistance of the cemented carbide-reinforced silicon-manganese bainitic steel.

[0010] Preferably, in S1, based on the mass of the modified TiC particles, modified B4C particles, and CoCrFeNiAl2Ti2 high-entropy alloy binder phase as 100%, the mass percentage of the modified TiC particles is 65%~68%, the mass percentage of the modified B4C particles is 22%~25%, and the mass percentage of the CoCrFeNiAl2Ti2 high-entropy alloy binder phase is 8%~10%.

[0011] Preferably, in S1, the thickness of the transition metal element coating in the modified TiC particles is 0.5~1.5μm.

[0012] More preferably, in S1, the transition metal element coating is a nickel coating or a cobalt coating.

[0013] It should be noted that in S1, the modified TiC particles can be prepared by chemical plating, and the specific chemical plating method is described in invention patent 202411132518.0.

[0014] Preferably, in S1, the thickness of the metal oxide layer in the modified B4C particles is 100~300nm.

[0015] More preferably, in S1, the metal oxide layer is a yttrium oxide layer or an aluminum oxide layer.

[0016] More preferably, in step S1, the method for preparing the modified B4C particles includes the following steps: Step a: Add B4C particles to nitric acid solution for activation, separate solid and liquid, wash, and dry to obtain activated B4C particles; Step b: Add the metal source to the alcohol solution, then add citric acid, adjust the pH to 2-4 with ammonia, and keep it at 60-80℃ to obtain the gel solution; Step c: Add the activated B4C particles to the gel solution, keep warm at 40~60℃, separate the solid and liquid, dry, and calcine at 600~900℃ to obtain the modified B4C particles.

[0017] More preferably, in step a, the B4C particles further include the following pretreatment: the B4C particles are added to anhydrous ethanol for ultrasonic cleaning, and then dried.

[0018] More preferably, in step a, the concentration of the nitric acid solution is 5 vol% to 10 vol.

[0019] More preferably, in step a, the activation time is 1 to 2 hours.

[0020] More preferably, in step b, the metal source is either a yttrium source or an aluminum source.

[0021] More preferably, the yttrium source is yttrium nitrate.

[0022] More preferably, the aluminum source is aluminum isopropoxide.

[0023] More preferably, in step b, the molar concentration of the metal source in the alcohol solution is 0.5~1 mol / L.

[0024] More preferably, in step b, the volume ratio of water to anhydrous ethanol in the alcohol solution is (2~2.2):1.

[0025] More preferably, in step b, the molar ratio of metal ions to citric acid in the metal source is 1:(1~3).

[0026] More preferably, in step b, the ammonia water is further diluted with 9 times its volume of water before use.

[0027] More preferably, in step b, the heat preservation time is 1 to 3 hours.

[0028] For example, the heat preservation process also includes a stirring process. The specific parameters of the stirring process are not further limited here, and it can be operated according to the conventional technical means mastered by those skilled in the art.

[0029] More preferably, in step c, the amount of activated B4C particles added is 20wt% to 30wt% of the mass of the adhesive solution.

[0030] More preferably, in step c, the heat preservation time is 1 to 2 hours.

[0031] More preferably, in step c, the drying conditions include: a temperature of 80~120℃ and a time of 12~24h.

[0032] More preferably, in step c, the temperature is increased to 600-900°C at a rate of 2-5°C / min.

[0033] More preferably, in step c, the calcination time is 2-4 hours.

[0034] More preferably, in S1, based on the mass of the modified TiC particles as 100%, the mass percentage of modified TiC particles with a particle size of 10~25μm is 60%~70%, and the mass percentage of modified TiC particles with a particle size of 2~5μm is 30%~40%.

[0035] The modified TiC particles provided by this invention include particles with a particle size of 10-25 μm and particles with a particle size of 2-5 μm. Using particles of different sizes helps to increase the particle packing density, suppress abnormal grain growth during sintering, and form a multi-scale strengthening effect. Among them, the large-size modified TiC particles provide a wear-resistant skeleton, resist micro-cutting, and significantly improve the wear resistance of the material; the small-size modified TiC particles and modified B4C particles suppress lath bundle growth and pin dislocations during the bainitic phase transformation, achieving a dispersion strengthening effect, further improving the hardness and wear resistance of cemented carbide-reinforced silicon-manganese bainitic steel.

[0036] Preferably, in S1, the particle size of the modified B4C particles is 1~3μm.

[0037] Preferably, in S1, the particle size of the CoCrFeNiAl2Ti2 high-entropy alloy binder phase is 5~10μm.

[0038] More preferably, in S1, the molar ratio of Co, Cr, Fe, Ni, Al and Ti in the CoCrFeNiAl2Ti2 high-entropy alloy binder phase is 1:1:1:1:2:2.

[0039] In this invention, any CoCrFeNiAl2Ti2 high-entropy alloy that meets the above conditions can achieve a comparable effect.

[0040] For example, in S1, the uniform mixing is achieved by wet milling. Specifically, the ball-to-material ratio is 8:1 during wet milling, and the amount of anhydrous ethanol added is no longer limited. It can be operated according to the conventional methods known to those skilled in the art.

[0041] For example, the ball milling time during the wet milling process is 4 to 6 hours and the rotation speed is 200 to 300 rpm.

[0042] For example, after ball milling, the process also includes drying in a vacuum drying oven at 60~80℃ for 12 hours and passing through a 120-mesh sieve.

[0043] For example, in S1, the sintering is carried out in a vacuum hot press sintering furnace.

[0044] Preferably, in S1, the temperature is increased to 1200~1350℃ at a rate of 5~10℃ / min.

[0045] Preferably, in S1, the sintering pressure is 30~45MPa.

[0046] Preferably, in S1, the sintering time is 60~120 min.

[0047] Preferably, in S1, the cooling method is to cool the furnace to room temperature while cooling, ensuring a vacuum degree ≤10.-2 Pa.

[0048] Preferably, in S2, the molten silicon-manganese bainitic steel comprises the following chemical composition by mass percentage: C: 0.65%~0.78%, Si: 2.13%~2.36%, Mn: 2.27%~2.49%, Cr: 0.84%~0.97%, Mo: 0.28%~0.39%, Ni: 0.47%~0.62%, Nb: 0.035%~0.066%, V: 0.061%~0.094%, Ca: 0.028%~0.055%, P≤0.035%, S≤0.03%, with the balance being Fe and unavoidable impurities.

[0049] The molten steel of silicon-manganese bainitic steel contains microalloying elements such as vanadium and niobium, which can further refine the grains, eliminate the coarse columnar and dendritic structures in the cast state, and improve the toughness of cemented carbide-reinforced silicon-manganese bainitic steel.

[0050] Preferably, in S2, the particle size of the rare earth magnesium silicon iron alloy is 3~8mm.

[0051] Preferably, in S2, the rare earth magnesium silicon iron alloy comprises the following chemical composition by mass percentage: Mg: 10.86%~11.41%, RE: 2.05%~2.38%, Si: 40.19%~41.92%, Ca: 2.18%~2.6%, with the balance being Fe and unavoidable impurities.

[0052] More preferably, RE includes La and Ce. The present invention does not further limit the specific amount of La and Ce, as long as the total amount is satisfied.

[0053] This invention introduces rare earth elements into cemented carbide-reinforced silicon-manganese bainitic steel by adding rare earth magnesium-silicon ferroalloy. This improves the as-cast crystal structure, refining grains, purifying grain boundaries, and removing harmful inclusions, thereby enhancing the toughness of the cemented carbide-reinforced silicon-manganese bainitic steel. The purifying effect of rare earth elements in cemented carbide-reinforced silicon-manganese bainitic steel is mainly reflected in the following aspects: rare earth elements can significantly reduce the content of oxygen and sulfur, and reduce the harmful effects of low-melting-point elements such as phosphorus, sulfur, hydrogen, arsenic, antimony, bismuth, lead, or tin; magnesium has a low melting and boiling point and is easily vaporized under the action of high-temperature molten steel, promoting the turbulence of molten steel in the ladle and ensuring that the cemented carbide is evenly distributed in the molten steel, which is conducive to further improving the strength, toughness, and hardness of cemented carbide-reinforced silicon-manganese bainitic steel.

[0054] Preferably, in S2, the amount of rare earth magnesium silicon iron alloy added is 1% to 1.2% of the total mass of the silicon manganese bainitic steel molten steel.

[0055] Preferably, in S2, the particle size of the cemented carbide is 150~220 mesh.

[0056] Preferably, in S2, the amount of cemented carbide added is 13% to 15% of the total mass of the molten silicon-manganese bainitic steel.

[0057] Preferably, in S2, the molten steel needs to be cooled to 1517~1533℃ during casting.

[0058] Preferably, in step S2, after the casting is completed, the process also includes sand removal and polishing.

[0059] Preferably, in step S3, the heat preservation time is 90~120 minutes.

[0060] Preferably, in S3, the salt bath time is 120-150 minutes.

[0061] Preferably, in S3, the salt bath reagents used in the salt bath include potassium nitrate and sodium nitrate.

[0062] More preferably, in S3, based on the total mass of the salt bath reagent as 100%, the mass percentage of potassium nitrate is 40%~45%, and the mass percentage of sodium nitrate is 55%~60%.

[0063] This invention provides a cemented carbide-reinforced silicon-manganese bainitic steel, which is prepared by the above-mentioned method for preparing cemented carbide-reinforced silicon-manganese bainitic steel. Attached Figure Description

[0064] Figure 1 The metallographic structure of the cemented carbide-reinforced silicon-manganese bainitic steel provided in Embodiment 1 of the present invention is shown in the figure. Figure 2 This is a SEM image of the modified TiC particles provided in Example 1 of the present invention. Detailed Implementation

[0065] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments and accompanying drawings. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0066] The method for preparing a nickel coating in modified TiC particles provided in this embodiment of the invention includes the following steps: (1) Cleaning: Take an appropriate amount of TiC particles, soak them in anhydrous ethanol at room temperature, and clean them in an ultrasonic cleaner for 5 minutes. (2) Roughening: After cleaning, TiC particles are washed three times with deionized water to remove as much residual anhydrous ethanol as possible. Then they are dried and then soaked in the roughening solution for 10 minutes. The reaction vessel must be shaken continuously during soaking. The roughening solution is prepared by mixing 10 mL of 40% hydrofluoric acid and an appropriate amount of deionized water to make 200 mL. The ratio of hydrofluoric acid to deionized water is 1:19. (3) Sensitization: Wash the TiC particles after the roughening step three times with deionized water to remove residual hydrofluoric acid. Then, put the TiC particles into the prepared sensitization solution and soak for 30 minutes. During soaking, the reaction vessel must be shaken continuously. The main component of the sensitization solution is 0.06 mol / L SnCl2·2H2O. When preparing 200 mL of sensitization solution, weigh out SnCl2·2H2O solid and add it to an appropriate amount of deionized water. The solution will turn milky white. Then add an appropriate amount of hydrochloric acid to make the stannous chloride solution clear. Then add deionized water until the sensitization solution reaches 200 mL. During the sensitization process, the reaction vessel needs to be shaken many times to allow more divalent tin ions to adhere to the small pits on the surface of the TiC particles. (4) Activation: Place the sensitized TiC particles into the activation solution and soak for 20 minutes. During soaking, the reaction vessel must be continuously shaken. The main component of the activation solution is 0.0022 mol / L PdCl2. To prepare the activation solution, first weigh the PdCl2 particles and add them to deionized water, then add hydrochloric acid. The solution will turn brownish-yellow. Continue stirring until the PdCl2 is completely dissolved. During the activation process, the reaction vessel must be shaken multiple times to ensure the PdCl2 is dissolved. 2+ As much as possible, it is reduced to metallic Pd, and a large number of Pd catalytic nuclei are covered on the surface of TiC particles; (5) Chemical plating: A nickel plating layer is deposited on the surface of TiC particles after decontamination, roughening, sensitization and activation by chemical plating. The chemical plating solution formula is 20 g / L NiSO4, 18 g / L C6H8O7, 12 mL / L C3H6O3, 8 mg / L (NH4)2MoO4, 35 g / L NaH2PO2 and 25 g / L CH3COONa. During the chemical plating process, the chemical plating solution is heated in a water bath to maintain the temperature at 80℃ and the pH at 5~5.2. The plating is carried out until the coating thickness is 0.5~1.5 μm to obtain modified TiC particles.

[0067] The method for preparing a cobalt coating in modified TiC particles provided in this embodiment of the invention includes the following steps: (1) Cleaning: Take an appropriate amount of TiC particles, soak them in anhydrous ethanol at room temperature, and clean them in an ultrasonic cleaner for 5 minutes. (2) Roughening: After cleaning, TiC particles are washed three times with deionized water to remove as much residual anhydrous ethanol as possible. Then they are dried and then soaked in the roughening solution for 10 minutes. The reaction vessel must be shaken continuously during soaking. The roughening solution is prepared by mixing 10 mL of 40% hydrofluoric acid and an appropriate amount of deionized water to make 200 mL. The ratio of hydrofluoric acid to deionized water is 1:19. (3) Sensitization: Wash the TiC particles after the roughening step three times with deionized water to remove residual hydrofluoric acid. Then, put the TiC particles into the prepared sensitization solution and soak for 30 minutes. During soaking, the reaction vessel must be shaken continuously. The main component of the sensitization solution is 0.08 mol / L SnCl2·2H2O. When preparing 200 mL of sensitization solution, weigh out SnCl2·2H2O solid and add it to an appropriate amount of deionized water. The solution will be milky white. Then add an appropriate amount of hydrochloric acid to make the stannous chloride solution clear. Then add deionized water until the sensitization solution reaches 200 mL. During the sensitization process, the reaction vessel needs to be shaken many times to allow more divalent tin ions to adhere to the small pits on the surface of the TiC particles. (4) Activation: Place the sensitized TiC particles into the activation solution and soak for 20 minutes. During soaking, the reaction vessel must be continuously shaken. The main component of the activation solution is 0.0024 mol / L PdCl2. To prepare the activation solution, first weigh the PdCl2 particles and add them to deionized water, then add hydrochloric acid. The solution will turn brownish-yellow. Continue stirring until the PdCl2 is completely dissolved. During the activation process, the reaction vessel must be shaken multiple times to ensure the PdCl2 is dissolved. 2+ As much as possible, it is reduced to metallic Pd, and a large number of Pd catalytic nuclei are covered on the surface of TiC particles; (5) Chemical plating: Cobalt coating is deposited on the surface of TiC particles after decontamination, roughening, sensitization and activation by chemical plating. The chemical plating solution formula is 25 g / L CoSO4, 16 g / L C6H8O7, 10 mL / L C3H6O3, 10 mg / L (NH4)2MoO4, 30 g / L NaH2PO2 and 30 g / L CH3COONa. During the chemical plating process, the chemical plating solution is heated in a water bath to maintain the temperature at 85℃ and the pH at 5~5.2. The plating is carried out until the coating thickness is 0.5~1.5 μm to obtain modified TiC particles.

[0068] The method for preparing the yttrium oxide layer in modified B4C particles provided in this embodiment of the invention includes the following steps: Step a: Add B4C particles to anhydrous ethanol and ultrasonically clean for 30 min, dry thoroughly at 100℃, then add to a 10 vol% nitric acid solution for activation for 1 h, separate solid and liquid, wash with deionized water until neutral, and dry to obtain activated B4C particles. Step b: Based on a yttrium nitrate concentration of 1 mol / L, dissolve yttrium nitrate in anhydrous ethanol solution with a water-to-ethanol volume ratio of 2:1. Then, based on a yttrium ion-to-citric acid molar ratio of 1:1, add citric acid. Mix ammonia and water in a volume ratio of 1:9. Adjust the pH of the mixture to 2-4 and heat it in a constant temperature water bath at 80°C for 2 hours to obtain a gel solution. Step c: Add 20 wt% of activated B4C particles to the sol solution and stir at 50°C for 1 h to allow the sol to fully wet and adsorb onto the surface of the activated B4C particles. Then let it stand to promote the gelation transformation of the sol on the particle surface, forming a wet gel film. Separate the gel-coated activated B4C particles from the remaining sol using a centrifuge, dry at 100°C for 20 h, heat to 800°C at a rate of 4°C / min, calcine for 3 h, and cool to room temperature in the furnace to form a dense yttrium oxide layer.

[0069] The method for preparing the alumina layer in modified B4C particles provided in this embodiment of the invention includes the following steps: Step a: Add B4C particles to anhydrous ethanol and ultrasonically clean for 30 min, dry thoroughly at 100℃, then add to a 10 vol% nitric acid solution for activation for 2 h, separate solid and liquid, wash with deionized water until neutral, and dry to obtain activated B4C particles. Step b: Based on the concentration of aluminum isopropoxide being 1 mol / L, add aluminum isopropoxide to anhydrous ethanol solution. The volume ratio of water to anhydrous ethanol in the anhydrous ethanol solution is 2:1. Then, based on the molar ratio of aluminum ions to citric acid being 1:2, add citric acid. Mix ammonia and water in a volume ratio of 1:9. Adjust the pH of the above mixture to 2-4. Stir and heat in a constant temperature water bath at 80°C for 2 hours to obtain the gel solution. Step c: Add 20wt% of activated B4C particles to the sol solution and stir at 50℃ for 1h to allow the sol to fully wet and adsorb onto the surface of the activated B4C particles. Then let it stand to promote the gelation transformation of the sol on the particle surface, forming a wet gel film. Separate the gel-coated activated B4C particles from the remaining sol using a centrifuge, dry at 100℃ for 20h, heat to 700℃ at a rate of 4℃ / min, calcine for 3h, and cool to room temperature with the furnace to form a dense alumina layer.

[0070] Example 1 This embodiment provides a method for preparing cemented carbide-reinforced silicon-manganese bainitic steel, comprising the following steps: S1. Pretreatment of reinforcing phase particles: Modified TiC particles: Chemical nickel plating is performed on the surface of TiC particles, and the coating thickness is controlled at 0.5~1.5μm; Modified B4C particles: A nano-yttrium oxide (Y2O3) barrier layer is coated on the surface of B4C particles using the sol-gel method, with a thickness of 100~300nm; S2. Mixing and Ball Milling: Based on the mass of modified TiC particles, modified B4C particles, and CoCrFeNiAl2Ti2 high-entropy alloy binder phase as 100%, 65% of modified TiC particles, 25% of modified B4C particles, and 10% of CoCrFeNiAl2Ti2 high-entropy alloy binder phase are mixed. The mass percentage of modified TiC particles with a particle size of 10~25μm is calculated as follows: The modified TiC particles, with a particle size of 2-5 μm, comprised 60% of the total mass, while the modified B4C particles comprised 1-3 μm. The CoCrFeNiAl2Ti2 high-entropy alloy binder phase comprised 5-10 μm. Wet milling was performed using a planetary ball mill with a ball-to-material ratio of 8:1, using anhydrous ethanol as the medium. The milling time was 4 hours, and the milling speed was 300 rpm. After milling, the slurry was dried in a vacuum drying oven at 60℃ for 12 hours and then passed through a 120-mesh sieve. S3. Hot Press Sintering and Crushing: The material that passed through the sieve in S2 is loaded into a graphite mold and sintered in a vacuum hot press sintering furnace. The process parameters are as follows: heating rate: 5℃ / min; sintering temperature: 1200℃; pressure: pressure is applied starting at 600℃, with a final pressure of 30MPa, and pressure is maintained until sintering is complete; holding time: 120min; cooling method: cooling to room temperature with the furnace, maintaining a vacuum degree ≤10. -2 Pa, then the cemented carbide is crushed to 150~220 mesh to obtain cemented carbide; S4. A medium-frequency induction furnace is used to melt ferrosilicon-manganese bainitic steel. First, scrap steel, carbon raiser, ferrochrome, ferromolybdenum, nickel plate, and ferroniobium are mixed and heated to melt. After the molten steel is cleared, ferrosilicon, ferromanganese, ferrovanadium, and silicon-calcium alloy are added sequentially. The chemical composition and mass fraction of the molten steel in the furnace are controlled at 0.65%C, 2.36%Si, 2.27%Mn, 0.97%Cr, 0.28%Mo, 0.62%Ni, 0.035%Nb, 0.094%V, 0.028%Ca, 0.031%P, 0.028%S, with the balance being Fe and unavoidable impurities. The molten steel is heated to 1653℃, and then poured into a ladle. Rare earth magnesium ferrosilicon alloy with a particle size of 3-8mm is pre-added to the bottom of the ladle (the chemical composition and mass fraction of the rare earth magnesium ferrosilicon alloy are: 10.86% Mg, 2.38%...). (La+Ce, 40.19% Si, 2.6% Ca, balance Fe and unavoidable impurities), rare earth magnesium silicon iron alloy is topped with 150~220 mesh cemented carbide particles obtained by S3. The addition of rare earth magnesium silicon iron alloy particles and cemented carbide particles accounts for 1% and 13% of the mass fraction of the molten steel entering the ladle, respectively. After slag removal and settling, the molten steel in the ladle is poured directly into the mold when the temperature drops to 1517℃. After the molten steel solidifies, the casting is removed from the mold and then cleaned and polished. S5. Subsequent heat treatment: After sand removal and grinding, the casting is placed in a box-type resistance furnace and heated to 920℃. It is held at this temperature for 120 minutes and then quickly transferred to a salt bath furnace at 280℃ (with the total mass of the salt bath reagent being 100%, the mass percentage of potassium nitrate being 40%, and the mass percentage of sodium nitrate being 60%). It is held at this temperature for 120 minutes. After the isothermal treatment, it is taken out and air-cooled to room temperature to obtain cemented carbide reinforced silicon-manganese bainitic steel.

[0071] Example 2 This embodiment provides a method for preparing cemented carbide-reinforced silicon-manganese bainitic steel, comprising the following steps: S1. Pretreatment of reinforcing phase particles: Modified TiC particles: Chemical cobalt plating is performed on the surface of TiC particles, and the coating thickness is controlled at 0.5-1.5μm; Modified B4C particles: A nano-alumina (Al2O3) barrier layer is coated on the surface of B4C particles using the sol-gel method, with a thickness of 100-300 nm. S2. Mixing and Ball Milling: Based on the mass of modified TiC particles, modified B4C particles, and CoCrFeNiAl2Ti2 high-entropy alloy binder phase as 100%, 68% of modified TiC particles, 23% of modified B4C particles, and 9% of CoCrFeNiAl2Ti2 high-entropy alloy binder phase are mixed. The mass percentage of modified TiC particles with a particle size of 10~25μm is calculated as follows: The modified TiC particles, with a particle size of 2-5 μm, comprised 70% of the total mass, while the modified B4C particles comprised 1-3 μm. The CoCrFeNiAl2Ti2 high-entropy alloy binder phase comprised 5-10 μm. Wet milling was performed using a planetary ball mill with a ball-to-material ratio of 8:1, using anhydrous ethanol as the medium. The milling time was 6 hours, and the milling speed was 200 rpm. The slurry after milling was dried in a vacuum drying oven at 80℃ for 12 hours and then passed through a 120-mesh sieve. S3. Hot Press Sintering and Crushing: The material that passed through the sieve in S2 is loaded into a graphite mold and sintered in a vacuum hot press sintering furnace. The process parameters are as follows: heating rate: 10℃ / min; sintering temperature: 1350℃; pressure: pressure is applied starting at 600℃, with a final pressure of 45MPa, and pressure is maintained until sintering is complete; holding time: 60min; cooling method: cooling to room temperature with the furnace, maintaining a vacuum degree ≤10. -2 Pa, then the cemented carbide is crushed to 150~220 mesh to obtain cemented carbide; S4. A medium-frequency induction furnace is used to melt ferrosilicon-manganese bainitic steel. First, scrap steel, carbon raiser, ferrochrome, ferromolybdenum, nickel plate, and ferroniobium are mixed and heated to melt. After the molten steel is cleared, ferrosilicon, ferromanganese, ferrovanadium, and silicon-calcium alloy are added sequentially. The chemical composition and mass fraction of the molten steel in the furnace are controlled at 0.78% C, 2.13% Si, 2.49% Mn, 0.84% ​​Cr, 0.39% Mo, 0.47% Ni, 0.066% Nb, 0.061% V, 0.055% Ca, 0.026% P, 0.021% S, with the balance being Fe and unavoidable impurities. The molten steel is heated to 1668℃, and then tapped into a ladle. Rare earth magnesium ferrosilicon alloy with a particle size of 3-8 mm is pre-added to the bottom of the ladle (the chemical composition and mass fraction of the rare earth magnesium ferrosilicon alloy are: 11.41% Mg, 2.05 ... (La+Ce, 41.92% Si, 2.18% Ca, balance Fe and unavoidable impurities), rare earth magnesium silicon iron alloy is topped with 150-220 mesh cemented carbide particles obtained from S3. The rare earth magnesium silicon iron alloy particles and cemented carbide particles account for 1.2% and 15% of the mass fraction of the molten steel entering the ladle, respectively. After slag removal and settling, the molten steel in the ladle is poured directly into the mold when the temperature drops to 1533℃. After the molten steel solidifies, the casting is removed from the mold and then cleaned and polished. S5. Subsequent heat treatment: After sand removal and grinding, the casting is placed in a box-type resistance furnace and heated to 950℃. It is held at this temperature for 90 minutes and then quickly transferred to a salt bath furnace at 320℃ (based on the total mass of the salt bath reagent being 100%, the mass percentage of potassium nitrate being 45%, and the mass percentage of sodium nitrate being 55%). It is held at this temperature for 150 minutes. After the isothermal treatment, it is taken out and air-cooled to room temperature to obtain cemented carbide reinforced silicon-manganese bainitic steel.

[0072] Example 3 This embodiment provides a method for preparing cemented carbide-reinforced silicon-manganese bainitic steel, comprising the following steps: S1. Pretreatment of reinforcing phase particles: TiC particles: Chemical cobalt plating is performed on the surface of TiC particles, and the coating thickness is controlled at 0.5~1.5μm; B4C particles: A nano-yttrium oxide (Y2O3) barrier layer is coated on the surface of B4C particles using the sol-gel method, with a thickness of 100~300nm; S2. Mixing and Ball Milling: Based on the mass of modified TiC particles, modified B4C particles, and CoCrFeNiAl2Ti2 high-entropy alloy binder phase as 100%, 67% of modified TiC particles, 25% of modified B4C particles, and 8% of CoCrFeNiAl2Ti2 high-entropy alloy binder phase are mixed. The mass percentage of modified TiC particles with a particle size of 10~25μm is calculated as follows: The modified TiC particles, with a particle size of 2-5 μm, comprised 65% of the total mass, while the modified B4C particles comprised 1-3 μm. The CoCrFeNiAl2Ti2 high-entropy alloy binder phase comprised 5-10 μm. Wet milling was performed using a planetary ball mill with a ball-to-material ratio of 8:1, using anhydrous ethanol as the medium. The milling time was 5 hours, and the milling speed was 250 rpm. The slurry after milling was dried in a vacuum drying oven at 70℃ for 12 hours and then passed through a 120-mesh sieve. S3. Hot Press Sintering and Crushing: The material that passed through the sieve in S2 is loaded into a graphite mold and sintered in a vacuum hot press sintering furnace. The process parameters are as follows: heating rate: 8℃ / min; sintering temperature: 1280℃; pressure: pressure is applied starting at 600℃, with a final pressure of 38MPa, and pressure is maintained until sintering is complete; holding time: 90min; cooling method: cooling to room temperature with the furnace, maintaining a vacuum degree ≤10. -2 Pa, then the cemented carbide is crushed to 150~220 mesh to obtain cemented carbide; S4. A medium-frequency induction furnace is used to melt ferrosilicon-manganese bainitic steel. First, scrap steel, carbon raiser, ferrochrome, ferromolybdenum, nickel plate, and ferroniobium are mixed and heated to melt. After the molten steel is cleared, ferrosilicon, ferromanganese, ferrovanadium, and silicon-calcium alloy are added sequentially. The chemical composition and mass fraction of the molten steel in the furnace are controlled at 0.72% C, 2.27% Si, 2.40% Mn, 0.88% Cr, 0.34% Mo, 0.49% Ni, 0.046% Nb, 0.083% V, 0.051% Ca, 0.034% P, 0.027% S, with the balance being Fe and unavoidable impurities. The molten steel is heated to 1664℃, and then tapped into a ladle. Rare earth magnesium ferrosilicon alloy with a particle size of 3-8mm is pre-added to the bottom of the ladle (the chemical composition and mass fraction of the rare earth magnesium ferrosilicon alloy are: 10.98% Mg, 2.26%). La+Ce, 41.75% Si, 2.47% Ca, balance Fe and unavoidable impurities), rare earth magnesium silicon iron alloy was topped with 150~220 mesh cemented carbide particles obtained by S3. The rare earth magnesium silicon iron alloy particles and cemented carbide particles accounted for 1.1% and 14% of the mass fraction of the molten steel entering the ladle, respectively. After slag removal and settling, the molten steel in the ladle was poured directly into the mold when the temperature dropped to 1526℃. After the molten steel solidified, the mold was opened and the casting was removed for sand removal and grinding. S5. Subsequent heat treatment: After sand removal and grinding, the casting is placed in a box-type resistance furnace and heated to 930℃. It is held at this temperature for 110 minutes and then quickly transferred to a 300℃ salt bath furnace (with the total mass of the salt bath reagent being 100%, the mass percentage of potassium nitrate being 42%, and the mass percentage of sodium nitrate being 58%). It is held at this temperature for 140 minutes. After the isothermal treatment, it is taken out and air-cooled to room temperature to obtain cemented carbide reinforced silicon-manganese bainitic steel.

[0073] The cemented carbide-reinforced silicon-manganese bainitic steel provided in this embodiment of the invention was tested, and the specific test indicators and test performance are as follows: The testing standard for tensile strength is GB / T 228.1-2021; The standard for hardness testing is GB / T 230.1-2018; The testing standard for impact toughness is GB / T 229-2020.

[0074] Table 1 The wear resistance of the cemented carbide-reinforced silicon-manganese bainitic steel provided in the example was tested using an M-200 wear testing machine (MRH-3W). The test was conducted according to the requirements of GB / T 12444-2006. A GCr15 ring was selected as the friction pair. The hardness of the GCr15 ring is 62 HRC. The cemented carbide-reinforced silicon-manganese bainitic steel was cut into pieces with dimensions of (19×12×12) mm. 3 The metal block was used as the wear test sample. The specific test parameters were: wear speed of 200 r / min, test load of 196 N, and wear time of 2 h. The samples after ultrasonic cleaning with alcohol before and after wear were weighed using a high-precision electronic balance. The wear resistance of the material was characterized by the reciprocal of the wear loss. The wear resistance of the cemented carbide reinforced silicon-manganese bainitic steel provided in this embodiment of the invention reached 14.3~15.8 min / mg, while the wear resistance data of commonly used bainitic steel ZGM65Cr2Si2MnMo is 3.8 min / mg, and the wear resistance data of Cr15Mo3 high chromium cast iron is 10.6 min / mg. The cemented carbide-reinforced silicon-manganese bainitic steel prepared by the method provided in this invention possesses high strength (tensile strength ≥1500MPa), high hardness (≥62HRC), excellent impact toughness (≥20J / cm²), and superior wear resistance. Compared with commonly used bainitic steel and Cr15Mo3 high-chromium cast iron, its wear resistance is improved by 276.3% and 34.9%, respectively. The cemented carbide-reinforced silicon-manganese bainitic steel provided by this invention has good prospects for widespread application in the field of wear resistance.

[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions or improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing cemented carbide-reinforced silicon-manganese bainitic steel, characterized in that, Includes the following steps: S1. Modified TiC particles, modified B4C particles, and CoCrFeNiAl2Ti2 high-entropy alloy binder phase are mixed evenly, then heated to 1200~1350℃ for sintering, and cooled to obtain cemented carbide; wherein, in S1, the modified TiC particles are TiC particles coated with transition metal element coating, and the modified B4C particles are B4C particles coated with metal oxide coating. S2. The raw materials for ferrosilicon bainitic steel are smelted to obtain ferrosilicon bainitic steel molten steel; the ferrosilicon bainitic steel molten steel is heated to 1653~1668℃, and then poured into a ladle containing rare earth magnesium silicon ferroalloy and the hard alloy in sequence from bottom to top; slag is removed, and casting is performed to obtain a casting; wherein, the Si content in the ferrosilicon bainitic steel molten steel is 2.13%~2.36%; S3. The casting is kept at 920~950℃ and then subjected to a salt bath at 280~320℃ to obtain hard alloy reinforced silicon manganese bainitic steel.

2. The method for preparing cemented carbide-reinforced silicon-manganese bainitic steel as described in claim 1, characterized in that, In S1, based on the mass of the modified TiC particles, modified B4C particles, and CoCrFeNiAl2Ti2 high-entropy alloy binder phase being 100%, the mass percentage of the modified TiC particles is 65%~68%, the mass percentage of the modified B4C particles is 22%~25%, and the mass percentage of the CoCrFeNiAl2Ti2 high-entropy alloy binder phase is 8%~10%. In S1, the thickness of the transition metal element coating in the modified TiC particles is 0.5~1.5μm; In S1, the thickness of the metal oxide layer in the modified B4C particles is 100~300nm.

3. The method for preparing cemented carbide-reinforced silicon-manganese bainitic steel as described in claim 1 or 2, characterized in that, In S1, the transition metal element plating layer is a nickel plating layer or a cobalt plating layer; In S1, the metal oxide layer is a yttrium oxide layer or an aluminum oxide layer.

4. The method for preparing cemented carbide-reinforced silicon-manganese bainitic steel as described in claim 1 or 2, characterized in that, In S1, based on the mass of the modified TiC particles as 100%, the mass percentage of modified TiC particles with a particle size of 10~25μm is 60%~70%, and the mass percentage of modified TiC particles with a particle size of 2~5μm is 30%~40%.

5. The method for preparing cemented carbide-reinforced silicon-manganese bainitic steel as described in claim 1 or 2, characterized in that, In S1, the particle size of the modified B4C particles is 1~3μm; In S1, the particle size of the CoCrFeNiAl2Ti2 high-entropy alloy binder phase is 5~10μm.

6. The method for preparing cemented carbide-reinforced silicon-manganese bainitic steel as described in claim 1, characterized in that, In S1, the temperature is increased to 1200~1350℃ at a rate of 5~10℃ / min; In S1, the sintering pressure is 30~45MPa; In S1, the sintering time is 60~120min.

7. The method for preparing cemented carbide-reinforced silicon-manganese bainitic steel as described in claim 1, characterized in that, In S2, the molten silicon-manganese bainitic steel comprises the following chemical composition by mass percentage: C: 0.65%~0.78%, Si: 2.13%~2.36%, Mn: 2.27%~2.49%, Cr: 0.84%~0.97%, Mo: 0.28%~0.39%, Ni: 0.47%~0.62%, Nb: 0.035%~0.066%, V: 0.061%~0.094%, Ca: 0.028%~0.055%, P≤0.035%, S≤0.03%, with the balance being Fe and unavoidable impurities.

8. The method for preparing cemented carbide-reinforced silicon-manganese bainitic steel as described in claim 1, characterized in that, In S2, the particle size of the rare earth magnesium silicon iron alloy is 3~8mm; In S2, the rare earth magnesium silicon iron alloy comprises the following chemical composition by mass percentage: Mg: 10.86%~11.41%, RE: 2.05%~2.38%, Si: 40.19%~41.92%, Ca: 2.18%~2.6%, with the balance being Fe and unavoidable impurities; In S2, the amount of rare earth magnesium silicon iron alloy added is 1% to 1.2% of the total mass of the silicon manganese bainitic steel molten steel; In S2, the particle size of the cemented carbide is 150~220 mesh; In S2, the amount of cemented carbide added is 13% to 15% of the total mass of the molten silicon-manganese bainitic steel.

9. The method for preparing cemented carbide-reinforced silicon-manganese bainitic steel as described in claim 1, characterized in that, In S3, the heat preservation time is 90~120min; In S3, the salt bath time is 120-150 minutes.

10. A cemented carbide-reinforced silicon-manganese bainitic steel, characterized in that, It is prepared by the method of any one of claims 1 to 9 for hard alloy reinforced silicon-manganese bainitic steel.

Citation Information

Patent Citations

  • Modification method of ceramic particles, ceramic reinforced high chromium iron-based composite material and preparation method of ceramic reinforced high chromium iron-based composite material

    CN119243131A